(untitled) (The Batuk, 2019)
From psychological perspective, job satisfaction is the pleasant feelings that results from the appraisal of the job or by the job facilities. Job satisfaction is the level of contentment a person feels regarding his or her job. This feeling is based on an individual’s perception of satisfaction. Job satisfaction can be influenced by a person’s ability to complete required tasks, the earning, learning in an organization, and the way management treats employees. This research tries to study the level of job satisfaction on the basis of gender and their salary among college teachers of Lalitpur district. This survey research was conducted upon 122 (male 72 and female 50) respondents by using The Minnesota Satisfaction Questionnaire (MSQ). Result of study shows male respondents were earning more than female respondents. Male respondents are more satisfied than female. The job satisfaction is positively correlated to salary.